2020 14th European Conference on Antennas and Propagation (EuCAP) 2020
DOI: 10.23919/eucap48036.2020.9135889
|View full text |Cite
|
Sign up to set email alerts
|

Antenna Packaging For In-Body Applications

Abstract: A cylindrical mode expansion of the fields produced by an embedded antenna is used to determine the dimensions of the antenna packaging in order to minimize antenna impedance changes when the antenna is immersed in a varying dielectric medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The dielectric permittivity ranges from 1 to 84.5. Our results agreed with the previous theoretical analysis [10] and showed the expected behavior. The coating was an effective buffer that minimized the impact of the changing environment on antenna performance.…”
Section: A Final Design Of the Antenna And The Coatingsupporting
confidence: 93%
See 2 more Smart Citations
“…The dielectric permittivity ranges from 1 to 84.5. Our results agreed with the previous theoretical analysis [10] and showed the expected behavior. The coating was an effective buffer that minimized the impact of the changing environment on antenna performance.…”
Section: A Final Design Of the Antenna And The Coatingsupporting
confidence: 93%
“…Once the final design was chosen, we added the coating and readjusted the antenna size in accordance with the change in permittivity. The second stage was related to the coating design, for which we considered previous theoretical work [10]. Those authors showed how proper packaging can minimize changes in the antenna reactance due to differences in the surrounding dielectric medium.…”
Section: A Final Design Of the Antenna And The Coatingmentioning
confidence: 99%
See 1 more Smart Citation